Computational algorithms for multiphase magnetohydrodynamics and applications to accelerator targets - Samulyak, R.V.; Bo, W.; Li, X.; Kirk, H.; McDonald, K. (Condensed Matter Physics, 2010)
An interface-tracking numerical algorithm for the simulation of magnetohydrodynamic multiphase / free surface flows in the low-magnetic-Reynolds-number approximation of (Samulyak R., Du J., Glimm J., Xu Z., J. Comp. Phys., 2007, 226, 1532) is described. The algorithm has been implemented in multi-physics code FronTier and used for the simulation of MHD processes in liquids and weakly ionized plasmas. In this paper, numerical simulations of a liquid mercury jet entering strong and nonuniform magnetic field and interacting with a powerful proton pulse have been performed and compared with experiments. Such a mercury jet is a prototype of the proposed Muon Collider / Neutrino Factory, a future particle accelerator. Simulations demonstrate the elliptic distortion of the mercury jet as it enters the magnetic solenoid at a small angle to the magnetic axis, jet-surface instabilities (filamentation) induced by the interaction with proton pulses, and the stabilizing effect of the magnetic field. Описано інтерфейс-простежувальний числовий алгоритм для моделювання магнітогідродинамічних (MHD) потоків мультифаза/вільна поверхня у наближенні низькомагнітних чисел Рейнольдса (Samulyak R., Du J., Glimm J., Xu Z., J. Comp. Phys., 2007, 226, 1532). Алгоритм застосовується у мультифізичному коді FronTier і використовується для моделювання MHD процесів у рідині та слабко іонізованій плазмі. Числово змодельовано рідкий ртутний струмень, що входить у сильне та неоднорідне магнітне поле і взаємодіє з потужним протонним імпульсом, і порівняно з експериментом. Такий ртутний струмінь є прототипом запропонованого майбутнього прискорювача частинок Мюонний коллайдер/Нейтринна фабрика. У процесі моделювання продемонстровано еліптичну дисторцію ртутного струменя, коли він входить у магнітне поле за малого кута до магнітної осі, нестійкості струмінь-поверхня (філаментацію), індуковані взаємодією з протонними імпульсами, та стабілізувальний ефект магнітного поля.